P0395DEMOGRAPHIC AND CLINICAL CHARACTERISTICS OF RAPIDLY PROGRESSIVE GLOMERULONEPHRITIS IN TURKEY. (6th June 2020) - Aydin, Zeki; Turkmen, Kultigin; Dede, Fatih; Yasar, Emre; Ozturk, Savas; Aydin, Mehmet; Tatar, Erhan; SAHIN, Garip; Manga Sahin, Gulizar; Oto, Ozgur Akin; Sumnu, Abdullah; Eroglu, Eray; et al.
Abstract: Background and Aims: Rapidly progressive glomerulonephritis (RPGN) is a clinical condition that develops due to different etiologic causes, characterized by a rapid and progressive decrease in renal function and progresses to end-stage renal failure in weeks to months if not treated. In our study, diagnostic and demographic characteristics of patients diagnosed with RPGN by biopsy, clinical and laboratory findings in our country were investigated. Method: Data were obtained from national multicenter (47 centers) data entered into the Turkish Society of Nephrology Glomerular Diseases (TSN-GOLD) Working Group database between May 2009 and June 2019. Demographic characteristics such as age, sex, indications for biopsy, diagnosis of the glomerular diseases, comorbidities, laboratory and biopsy findings of all patients were recorded. The data presented is cross-sectional and includes application data for the biopsy period. According to their types, RPGN patients were classified as type 1 (anti-GBM related), type 2 (immunocomplex related) and type 3 (immune-negative; "pauci-immune"). Results: After exclusion of 46 patients with missing data, 200 patients (mean age 47.9 ± 16.7 years, 44% female) were included in the study which constitutes 5.2% of the total glomerulonephritis database (total number of patients: 3875). Hypertension was present in 62 patients (31.0%) and diabetes was present in 18 patients (9.0%). Renal biopsy was performed in 147 (73.5%) patients due to nephritic syndrome (RPGN included). 80.2% of the patients' biopsies were performed in nephrology clinics and 19.8% of them were performed in radiology clinics. ANCA positivity was found in 121 (60.5%) patients (proteinase 3-ANCA was positive in 55 and myeloperoxidase-ANCA positive in 66 patients). Type 1 RPGN was detected in 11 (5.5%), type 2 RPGN in 42 (21%) and type 3 RPGN in 147 (73.5%) patients. In 21 patients (10.5%), biopsy revealed RPGN with advanced chronic changes (fibrous global sclerotic glomeruli, advanced interstitial fibrosis and tubular atrophy). Mean serum creatinine was 4.2 ± 3.4 mg/dl, median glomerular filtration rate was 18 (10-37) ml/min and proteinuria 2100 (1229-3526) mg/day according to CKD-EPI formula. The mean number of glomeruli in the biopsies was 18.8 ± 10.6 and the number of crescentic glomeruli was 9.9 ± 7.7 (ratio: 52.7%) (Figure). The patients were divided into 3 groups according to their crescentic glomeruli ratios. The proportion of crescentic glomeruli is 10-50% in group 1, 50-80% in group 2, and > 80% in group 3. The demographic, laboratory and histopathological characteristics of the groups are given in Figure. It was observed that urea and creatinine increased and calcium and hemoglobin decreased with increasing crescentic glomerular ratio. Conclusion: Our study provides valuable demographic, clinical, laboratory and histopathological data about RPGN in our country. Our data are generally compatible with the literature. In our study, advanced chronic histopathological findings were prominent in the biopsy of 21 patients. Early biopsy should be performed to confirm the diagnosis of RPGN and to avoid unnecessary intensive immunosuppressive therapy. In addition to the treatments applied, detailed data, including patient and renal survival are needed.